Simultaneous single-shot measurement of temperature and pressure along a one-dimensional line by use of laser-induced thermal grating spectroscopy. - Stevens, R; Ewart, P (2006)
We report a new technique, based on laser-induced thermal grating spectroscopy (LITGS), for time- and space-resolved simultaneous measurement of temperature and pressure along a one-dimensional line. LITGS signals generated in NO2/N2 mixtures along a 5 mm line produce a time-varying image that is recorded on a streak camera. The temperature is derived with a precision of 0.3% from the streak images using a rapid Fourier method with a spatial resolution of 150 microm along the line. The principle of pressure measurement is demonstrated using a sequence of images, and a simple extension of the method to single-shot pressure measurement is discussed.